Optimization of grinding parameter when grind haynes 242 using water based titanium oxide (TiO2) nanocoolant - Sangeetha, Govindasamy (2012)
This thesis entitled Optimization of Grinding Parameter when grind Haynes 242 using water based Titanium Oxide (TiO2) Nanocoolant. The objective of this thesis is to find optimum parameter which is the Depth of cut. The thesis also is to investigate type of surface roughness and wheel wear produced during grinding process. Haynes 242 material was used as the work piece and Titanium Oxide as Nanocoolant was used for this grinding process. The another objective of this thesis is also to develop prediction model for surface roughness and wheel wear produced using Neural Network Analysis. These studies will be done for two experimental processes which is the single pass and multi pass experiment according to different depth of cut. As result, we observed that as the depth of cut increases, the surface roughness of the material also increases. However, when compare between the single pass and multi pass experiment, we can observed that surface roughness for single pass are much higher than the multi pass experiment. As for the recommendation, in future we can conduct the experiment using different kind of concentration, various depths of cut, different passes and also different types of material.